Botulinum toxin type A in treatment of chronic migraine, spasticity and bruxism - Kuliga, Klaudia; Dobko, Katarzyna; Frącz, Gabriela; Glac, Agata; Musz, Kinga; Sejnowska, Natalia; Socha, Agnieszka; Surowiec, Agata; Śnieżek, Kinga; Zając, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Nowadays, botulinum toxin has found use in many disease entities such as chronic migraine, spasticity, bruxism and many others. Among serotypes A-E, type A is mainly used in treatment. For the therapeutic effect to be maintained, injections need to be repeated most often after 12 weeks. More frequent injections of the toxin may result in the production of neutralizing antibodies. Aim of the study: The aim was to collect and analyze publications of application of botulinum toxin type A (BT-A) in the treatment of chronic migraine, spasticity and bruxism. Methods and materials: We reviewed the literature available in the PubMed database using the key words: “botulinum toxin”; “migraine”; “spasticity”; “bruxism”. Results: The use of botulinum toxin type A in patients with chronic migraine reduces the frequency of pain episodes and alleviates the symptoms. BT-A therapy reduces increased muscle tension, resulting in improved function of the upper or lower limb, facilitating the rehabilitation process, reducing pain associated with spasticity and protecting against the development of muscle contractures and secondary joint deformities. BT-A treatment of patients with bruxism reduces the level of pain and the maximum generated bite force, resulting in an improved quality of life for patients. Conclusion: Intramuscular administration of botulinum toxin is a safe, effective and minimally invasive method of treating chronic migraine, spasticity and bruxism. The botulinum toxin type A is the most studied serotype used for therapeutic purposes. Future research on botulinum toxin will certainly allow wider use.